2020
DOI: 10.1186/s12887-020-02218-2
|View full text |Cite
|
Sign up to set email alerts
|

The association of depression with child abuse among Indonesian adolescents

Abstract: Background: Depression is one of the most prevalent mental health problems among adolescents. Mental health problems might be the result of child abuse considering that their prevalences are increasing simultaneously in Indonesia. The aim of this study was to determine the association between depression and a history of abuse among adolescents. Methods: An analytic cross-sectional study was conducted on 786 junior high school students from Bandung City, West Java, Indonesia. Subjects were selected using two-st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 26 publications
1
13
0
2
Order By: Relevance
“…Like previous studies ( 1 3 , 41 ), the results of the present study demonstrate the link between childhood SES and depressive symptoms in young adults. Young adults from low-SES families exhibited more severe depressive symptoms than those from high-SES families, and depressive symptoms were significantly related to low childhood SES.…”
Section: Discussionsupporting
confidence: 88%
“…Like previous studies ( 1 3 , 41 ), the results of the present study demonstrate the link between childhood SES and depressive symptoms in young adults. Young adults from low-SES families exhibited more severe depressive symptoms than those from high-SES families, and depressive symptoms were significantly related to low childhood SES.…”
Section: Discussionsupporting
confidence: 88%
“…In terms of association between physical abuse, neglect and depression, our research revealed that more physical abuse and neglect were associated with higher depression, which supports several previous findings. According to a recent study [ 49 ], a history of childhood maltreatment was associated with depression in adolescents. All dimensions of childhood maltreatment had a significant association with depression, with psychological violence having the most impact on the occurrence of depression, followed by exposure to violence and physical violence.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to maltreatment during childhood has long been associated with an increased risk of subsequent psychological and behavioral problems across the human lifespan including mood disorders ( Norman et al, 2012 ; Lippard and Nemeroff, 2020 ), depression ( Dhamayanti et al, 2020 ), post-traumatic stress disorder ( McLaughlin et al, 2017 ; Schuck and Widom, 2019 ), borderline personality disorder ( Mainali et al, 2020 ), adult criminality ( Minh et al, 2013 ; Kim et al, 2016 ), and drug and substance abuse ( Elwyn and Smith, 2013 ; Mandavia et al, 2016 ). Studies have demonstrated that maltreatment histories are relatively common among individuals receiving treatment for substance and drug abuse ( Funk et al, 2003 ; Banducci et al, 2014 ; Loy et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%